ROLE OF MANAGEMENT IN THE HOSPITALITY INDUSTRY DURING A COVID-19 OUTBREAK - Anusha Pai, Dasharathraj K Shetty, B.H.S.Thimmappa, BM Zeeshan Hameed, Ankita Modi, Vathsala Patil, Nithesh Naik (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
It is essential to strengthening the hospitality industry infrastructure and management during the lockdown to stabilize the hospitality business and to move forward to make customers more comfortable. This paper presents the specific current situation where customers are becoming more cautious and the prospects of winning customer trust, based on a randomized survey of research papers. The broader management perspectives and clear vision for the economic future of this industry are emphasized. There is a need to take several quick, creative, and effective management steps responsibly to deal with the situation arising out of this health crisis. The hospitality industry can run with a minimum workforce adhering to safety, sanitization, and physical distancing norms, recognizing the lessons of this corona crisis. The consideration of consolidated recommendations on the strategic management of hotels and a people-oriented working strategy is a more sustainable exercise. It will be an opportunity for enterprises to leverage technology to create differentiation. The data connectivity and digital tools will become more critical in the practicality of this management solution in the post-pandemic period.